Metodologia para compressão de sinais de energia elétrica a partir de registros de forma de onda utilizando algorítmos genéticos e redes neurais artificiais - BARROS, Fabíola Graziela Noronha (Universidade Federal do Pará, 2017)
This thesis proposes a methodology for compression of electrical power signals from waveform records in electric systems, using genetic algorithm (GA) and artificial neural network (ANN).The genetic algorithm is used to select and preserve the points that better characterize the waveform contoursA and the artificial neural network is used in the compression of other points as well as on the signal reconstruction process. Thus, the data resulting are formed by a part of the original signal and by a compressed complementary part in the form of synaptic weights. The proposed methodology selects and preserves a percentage of the original signal samples, which are aspects not explored in the literature. The method was tested using field data obtained from an oscillographic recorder installed in a 230kV electrical power system. The results presented compression rates ranging from 88.36 to 95.86 for preservation rates ranging from 2.5 to 10 , respectively.